2007
DOI: 10.1038/sj.clpt.6100267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of OATP1B1 Genotype on the Pharmacokinetics of Rosuvastatin in Koreans

Abstract: This study was carried out to determine whether polymorphisms of organic anion-transporting polypeptide 1B1 (OATP1B1) have an effect on rosuvastatin pharmacokinetics in Koreans. Among 200 subjects genotyped for OATP1B1 c.388A>G, and c.521T>C, 30 subjects were selected for the rosuvastatin pharmacokinetic study. The area under the concentration-time curve for 0 to infinity (AUC(0-infinity)) of rosuvastatin for group 1 (*1a/*1a, *1a/*1b, *1b/*1b), group 2 (*1a/*15, *1b/*15), and group 3 (*15/*15) were 111+/-49.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 34 publications
7
70
1
1
Order By: Relevance
“…These studies were conducted after administration of a single 10 mg dose of rosuvastatin. 35,36 Although there are currently no clinical reports on the effects of the 521C allele on the efficacy of rosuvastatin to lower LDL-C levels, extrapolation of the aforementioned pharmacokinetic studies would point to a reduced response. In keeping with this hypothesis, we did observe a trend toward reduced efficacy of rosuvastatin in carriers of the 521C allele, but this did not reach statistical significance (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were conducted after administration of a single 10 mg dose of rosuvastatin. 35,36 Although there are currently no clinical reports on the effects of the 521C allele on the efficacy of rosuvastatin to lower LDL-C levels, extrapolation of the aforementioned pharmacokinetic studies would point to a reduced response. In keeping with this hypothesis, we did observe a trend toward reduced efficacy of rosuvastatin in carriers of the 521C allele, but this did not reach statistical significance (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cyclosporine A significantly increased systemic exposures of cerivastatin (1) and repaglinide (3) by inhibiting OATP1B1-mediated hepatic uptake (2). Genetic polymorphism of OATP1B1 (96-100) caused variation in the pharmacokinetics in human for many drugs such as fexofenadine (101), pitavastatin (102,103), pravastatin (104-110), repaglinide (111,112), rosuvastatin (113), temocapril (109), and valsartan (109). Although these data strongly suggest that the transporters are involved in the elimination process of drugs as much as the pharmacokinetics are affected by the perturbations of transporter activities, the quantitative prediction of overall intrinsic clearance (CL int,all in Eq.…”
Section: Prediction Of Tarnsporter-mediated Hepatic Uptake Clearance mentioning
confidence: 99%
“…However, for drugs that have a target inside the liver, decreased hepatic uptake by OATP1B1*15 might result in decreased pharmacological response and give rise to unforeseen toxic side effects. Indeed, it has been demonstrated that patients carrying the OATP1B1*15 variant show markedly increased plasma levels, decreased pharmacological response, and even increased extrahepatic toxicity, for instance, after pravastatin, pitavastatin, or rosuvastatin treatment (Niemi et al, 2004;Chung et al, 2005;Igel et al, 2006;Choi et al, 2008;Fahrmayr et al, 2010;Niemi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%